(untitled) (MAUSAM, 1975)
In on-line deployment of small computer systems with limited machine capability, the object of locating seismic sources atleast in the teleseismic distance range essentially requires, besides azimuth, accurate deduction of epicentral distance from apparent phase velocity in minimum operational steps. It has been shown that a seventh order polynomial in positive powers of apparent P-velocity yields reasonably precise distance estimates. The merits of this optimum relation have also been discussed in the light pf its application to the Gauribidanur Array real-time processing system.